Study on initial adoption of advanced driver assistance system: integrated model of PMT and UTAUT 2. (27th September 2019) - Jun, Jaehyeon; Park, Heejun; Cho, Insu
Abstract : Purpose: The purpose of this study is to verify factors affecting initial use intention of advanced driver assistance systems (ADAS) by adopting aspects of drivers' safety and convenience. Design/methodology/approach: As ADAS is developed for safety protection of driver, our study considers adopting not only models of technology acceptance but also models regarding safety protection. To achieve this research goal, a research model that integrates the protection motivation theory (PMT) and the extended unified theory of acceptance and use of technology (UTAUT2) is used to approach the technology acceptance process with an integrated perspective. We survey over two hundred people who had an experience of ADAS to verify our research model. Findings: By analysing the research model with structural equation modelling, we could identify which factors are influential on initial use intention of ADAS. There are some distinguished factors of success such as response efficacy, effort expectancy, performance expectancy and hedonic motivation. Originality/value: This study is expected to have a theoretical implication in terms of presenting a new research model and identifying the factors that affect the initial acceptance intention of ADAS and empirically analysing it. By analysing how users' diversified needs have impacts on initial use intention of ADAS, it is possible to predict the direction of the ADAS market for establishing a diffusion strategy and marketing strategy for the automobile market.